2017
DOI: 10.3928/01477447-20160926-08
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Atypical Compartment Syndrome Due to Proteus Infection

Abstract: Compartment syndrome is an orthopedic emergency with a multitude of etiologies. Although it is most commonly associated with trauma to the extremity, hematoma and infection are 2 rare etiologies of insidious compartment syndrome. Proteus mirabilis is an opportunistic gram-negative species that can infect the respiratory tract, urinary tract, and open wounds. The authors present the case of a 69-year-old woman who developed tissue necrosis and compartment syndrome secondary to an untreated hematoma infected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…[ 13 ] Current literature suggests that surgical fasciotomy of the involved compartments remains the gold-standard treatment approach, irrespective of the cause, condition, or location. [ 14 ] Stull et al[ 7 ] performed dualincision fasciotomy instead of a standard singleincision to avoid contamination of the uninvolved compartments in a patient with ACS secondary to a Proteus-infected hematoma. However, we decided to use a standard single-incision approach for our patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 13 ] Current literature suggests that surgical fasciotomy of the involved compartments remains the gold-standard treatment approach, irrespective of the cause, condition, or location. [ 14 ] Stull et al[ 7 ] performed dualincision fasciotomy instead of a standard singleincision to avoid contamination of the uninvolved compartments in a patient with ACS secondary to a Proteus-infected hematoma. However, we decided to use a standard single-incision approach for our patient.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review shows that unusual anatomical locations, rare conditions, drug interactions, and their side effects as well as surgical procedures and rare fractures can be associated with ACS. [ 7 , 13 , 14 ] There is limited knowledge about an infected hematoma associated with ACS,[ 7 ] and the authors of this case report describe a coinfection of forearm hematoma leading to ACS for the first time in the literature. [ 15 ] Proteus mirabilis and M. morganii were isolated as coinfectious agents in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from that, rare infections can cause the entity. Last year, Stull et al reported the case of a 6-year-old man treated for compartment syndrome caused by Proteus-infected hematoma of the lower leg [29].…”
Section: Unusual Conditionsmentioning
confidence: 99%